Single-fiber reflectance spectroscopy system using unmodified clinical laser fibers for tissue optical property recovery for photodynamic therapy treatment planning - Timothy M. Baran (Journal of Biomedical Optics, 2026)
SignificanceEstimation of tissue optical properties in workflow- and resource-constrained clinical settings is required to support photodynamic therapy (PDT) treatment planning, yet large-scale clinical translation remains limited by spectroscopy probe cost, complexity, and the need for probe-specific inverse models. Single-fiber reflectance (SFR) spectroscopy offers a simple and low-cost option, but previous implementations relied on customized angle-polished fibers.AimThe objective was to develop a proof-of-concept SFR spectroscopy system employing an unmodified, United States Food and Drug Administration (FDA)-approved clinical optical fiber for quantitative optical property extraction.ApproachA semi-empirical photon pathlength model was used to recover the absorption spectra μa(λ) and reduced scattering spectra μs′(λ) from tissue-mimicking phantoms containing methylene blue (MB) as the absorber and Intralipid-20% as the scatterer.ResultsOptical property retrieval from measurements acquired using three nominally identical fibers demonstrated clinically sufficient accuracy across fibers without requiring model adaptation. Across all fibers, MB concentration (CMB) was recovered with a root mean square error (RMSE) of 0.6 to 0.7 μM (p=0.88 among fibers), while μs′(665 nm) was recovered with an RMSE of 1.5 to 2.2 cm−1 (p=0.68 among fibers).ConclusionsWe demonstrate the potential of SFR spectroscopy using a standard clinical optical fiber as a scalable and clinically useful tool for tissue optical property estimation to support PDT treatment planning.